IDENTIFIKASI PENYEBAB KECELAKAAN KERJA PADA PROYEK KONSTRUKSI BANGUNAN GEDUNG TINGGI - Redaksi Tim Jurnal (FORUM MEKANIKA, 2018)
The most important resource in a construction project is labor, it is possible to cause errors that can disrupt the implementation. Thus the safety and health of the work must always be protected to prevent the occurrence of work accidents, for that effort is done by evaluating the cause of work accidents on construction projects. In this thesis, the issues raised are what are the dominant indicators of causes of occupational accidents and how to mitigate K3 on those dominant indicators. To know the dominant indicator, then do observation and interview with related personnel in the implementation of the construction project. Assessment of dominant indicators is obtained by scoring method using Likert scale. From the results of data analysis at PT. In total, respondents were 43 respondents (67%) with 27 indicators of occupational accidents due to K3 policy in Government Regulation No. 5 of 2012 already exist, but not yet done well, documentation does not exist, implementation of K3 has not been done in the field. And got the dominant indicator is from human factor with indicator A.3 equal to 95.56% that is behavior and habit careless. Factors that become obstacles in the implementation of OSH policy are human factor (HR), work tool factor, and working condition factor.